Some Aspects of the Development of Payment Innovations in the Kyrgyz Republic - Kantoroeva, Aijamal K.; Toktomamatova, Nurzat K. (International Journal of Criminology and Sociology, 2021)
This paper reveals the subject of payment innovations and their types, as well as presents analysis of the state and development of funds remittance using payment systems and growth of payments with plastic cards. In particular, it provides an overview of the number of payment cards in circulation in the regions and payment systems, reveals a picture of the development of money transfers that were carried out through international and local systems, as well as in the context of regions in terms of the volume of incoming payments. Disclosed measures and actions of the National Bank of the Kyrgyz Republic in the progress of a digital payment systems.